Quantum AI in Healthcare : Revolutionizing Diagnosis, Treatment and Drug Discovery (International Journal of Scientific Research in Science and Technology, 2024)
This paper explores the convergence of synthetic intelligence (AI) and quantum computing, unveiling its potential to revolutionize healthcare. By leveraging quantum mechanics’ standards, the paper examines how AI may be amplified to gain breakthroughs in clinical diagnoses, personalized treatment plans, and accelerated drug discovery. The exploration delves into how quantum simulations can model complex organic methods at a molecular level, permitting the prediction of remedy interactions and the layout of medicine with unequalled precision. Additionally, the paper discusses the combination of quantum sensors with AI for more suitable clinical imaging, capable of detecting diffused abnormalities. The transformative ability of this synergy is addressed, emphasizing its function in ushering in a brand new technology of personalised medicinal drug and efficient drug improvement.